Administrative Strategies for Effectiveness Elementary Schools in Khon Kean - Ngamzhaluai, Jaruek; Yurachai, Samret (Dhammathas Academic Journal, 2019)
This research aims to: 1) study administrative components for effectiveness of elementary schools in Khon Kean; 2) study current conditions, desirable components and needs for effective administration of elementary schools in Khon Kean; 3) develop This research aims to: 1) study administrative components for effectiveness of elementary schools in Khon Kean; 2) study current conditions, desirable components and needs for effective administration of elementary schools in Khon Kean; 3) develop administrative strategies for effectiveness of elementary schools in Khon Kean. The samples were 121 school directors, 121 heads of academic affairs and 121 chairmen of school boards. Research tools were five-rating scale, questionnaire, with IOC of 0.80-1.00. Reliability was 0.98. Computer processing program for data analysis was used. The research findings were as follows: 1. Current components of administration for effectiveness of elementary schools in Khon Kean consisted of 5 competencies: organization competency, academic leadership, learning process, atmosphere and environment, and community participation. 2. As for current components of administration for effectiveness of elementary schools in Khon Kean, among the highest were: organization competency, community participation, learning process, atmosphere and environment and academic leadership. Regarding desirable elements, among the highest were: community participation, organization competency, the process of learning, atmosphere and environment and academic leadership. Considering administrative strategy for effectiveness of elementary schools, in all, PNI was 0.36, with academic leadership PNI = 0.40, learning process, atmosphere and environment PNI = 0.36, community participation PNI = 0.34, organization competency PNI = 0.33. 3. With regard to develop administrative strategies for effectiveness of elementary schools in Khon kaen, five (5) strategies were found. Strategy 1: academic leadership with 1 goal, 4 sub-strategies and 4 indicators. Strategy 2: the process of learning with 1 goal, 6 Sub-strategies and 6 indicators. Strategy 3: atmosphere and environment with 1 goal, 4 sub-strategies and 4 indicators. Strategy 4: community participation with 2 goals, 4 sub-strategies and 4 indicators. Strategy 5: organization competency with 2 goals, 4 sub-strategies and 4 indicators.